MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI TEKNIK PENATAAN GAGASAN BAGI ANAK KESULITAN BELAJAR - Irmala Sari (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: This research was backgrounded by the problems that found in SDN 18 Koto Luar. A fourth grade child with learning dissabilities who has problems in reading comprehension. The study aims is to prove whether the structuring technique ideas can be used to improve the reading ability. This study used single subject research approach, with AB design. Based on the results shows a change from unstable with a tendency toward slight increases to the unstable positive. So, we can conclude that the structuring technique ideas can be used to improve reading comprehension for child with learning dissabilities in fourth grade at SDN 18 Koto Luar.